Teaching resources and achievement of specific competencies in wastewater engineering in environmental engineering students at the National Agrarian University La Molina, 2025 - Sánchez Márquez , Bruno Fidel (2026)
The objective of this study was to identify the relationship between the didactic resources used in the Wastewater Engineering course and the achievement of specific competencies among Environmental Engineering students at the Universidad Nacional Agraria La Molina (UNALM) during the 2025-I academic term. A quantitative approach was applied, with a non-experimental, cross-sectional, and correlational design. The instrument used was a Likert-type questionnaire administered to 34 students. A total of 76.5% of respondents reported medium use and 8.8% reported high use of the didactic resources evaluated. Among these, course-specific resources—such as laboratories and field trips—showed the highest level of high use (20.6%), while texts had the highest level of medium use (85.3%). The results showed a high and statistically significant correlation between the use of didactic resources and the achievement of specific competencies (sig. = 0.000; p = 0.747). Regarding the dimensions of these competencies, a high correlation was found with conceptual learning (sig. = 0.000; p = 0.715), highlighting the positive impact of texts and audiovisual materials. Procedural learning showed a moderate correlation (sig. = 0.000; p = 0.672), indicating the need to strengthen the use of ICTs, softwares, and practical activities. Finally, attitudinal learning also showed a moderate correlation (sig. = 0.000; p = 0.630), representing an opportunity to enhance contextualized resources that promote professional ethics, values, and environmental awareness.